Biomass, biopolymer-based materials, and bioenergy : construction, biomedical, and other industrial applications - Verma, Deepak; Fortunati, Elena; Jain, Siddarth; Zhang, Xiaolei (Woodhead Publishing series in composites science and engineering., 2019)
Biomass, Biopolymer-Based Materials and Bioenergy: Construction, Biomedical and Other Industrial Applications covers a broad range of material types, including natural fiber reinforced polymer composites, particulate composites, fiberboard, wood fiber composites, and plywood composite that utilize natural, renewable and biodegradable agricultural biomass. In terms of bioenergy, the authors explore not only the well-known processing methods of biofuels, but also the kinetics of biofuels production pathways, a techno-economic analysis on biomass gasification, and biomass gasification with further upgrading into diesel additives and hybrid renewable energy systems for power generation. Further chapters discuss advanced techniques for the development of biomass-based composites, biopolymer-based composites, biomass gasification, thermal kinetic design and techno-economic analysis of biomass gasification. By introducing these topics, the book highlights a totally new research theme in biopolymer-based composite materials and bioenergy.